2008
DOI: 10.1074/jbc.m801451200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IκB Kinase-related Kinases and Antiviral Responses by Tumor Suppressor CYLD

Abstract: The IB kinase (IKK)-related kinases, IKK⑀ and TBK1, participate in the induction of type I interferons (IFNs) during viral infections. Deregulated activation of IKK⑀ and TBK1 also contributes to the abnormal cell survival and transformation. However, how these kinases are negatively regulated remains unclear. We show here that the tumor suppressor CYLD has an essential role in preventing aberrant activation of IKK⑀/TBK1. CYLD deficiency causes constitutive activation of IKK⑀/TBK1, which is associated with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 45 publications
1
102
0
2
Order By: Relevance
“…For example, two ubiquitin E3 enzymes, TRIM25 and REUL (also called RNF135 and Riplet), have been demonstrated to catalyze K63-linked polyubiquitinations of RIG-I, which are critical for activation of RIG-I and signaling to downstream components [30][31][32]. Two DUBs, A20 and CYLD, have been demonstrated to remove the K63-linked polyubiquitin chains from RIG-I and thereby negatively regulate virus-induced type I IFN signaling [36,37]. On the other hand, RNF125 catalyzes K48-linked polyubiquitination of RIG-I and MDA5 on their N-terminal caspase recruitment domains (CARD) and these ubiquitinations cause proteasome-dependent degradation of RIG-I and MDA5, thereby negatively regulating virus-induced type I IFN signaling [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, two ubiquitin E3 enzymes, TRIM25 and REUL (also called RNF135 and Riplet), have been demonstrated to catalyze K63-linked polyubiquitinations of RIG-I, which are critical for activation of RIG-I and signaling to downstream components [30][31][32]. Two DUBs, A20 and CYLD, have been demonstrated to remove the K63-linked polyubiquitin chains from RIG-I and thereby negatively regulate virus-induced type I IFN signaling [36,37]. On the other hand, RNF125 catalyzes K48-linked polyubiquitination of RIG-I and MDA5 on their N-terminal caspase recruitment domains (CARD) and these ubiquitinations cause proteasome-dependent degradation of RIG-I and MDA5, thereby negatively regulating virus-induced type I IFN signaling [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several ubiquitin ligase enzymes have been identified to regulate these processes [28][29][30][31][32][33][34][35]. However, only a few DUBs are known to regulate these pathways: A20 was shown to negatively regulate the RIG-I-induced antiviral state [36], DUBA was identified to be required for efficient deubiquitination of TRAF3 and to function as a negative regulator of innate immune responses [25], and CYLD, known as a tumor suppressor, was recently reported to negatively regulate the activation of TBK1/ IKKε [37].…”
Section: Introductionmentioning
confidence: 99%
“…SOCS1, IRAK-M, and A20 have been identified as such negative regulators of the TLR-NF-B pathway (12)(13)(14). Additionally, DUBA, RNF125, SHP-2, Cyld, and A20 have been reported as negative regulators of the RLH-IRF3 pathway (15)(16)(17)(18)(19)(20)(21). In our previous study, we demonstrated that FLN29 protein induced by type I or II IFNs acts as a negative regulator for the TLR4-TRAF6 signaling pathway in macrophages.…”
mentioning
confidence: 93%
“…In contrast, the E3 ubiquitin ligase RNF125 catalyzes Lys 48 -linked ubiquitination of RIG-I and negatively regulates RIG-I-mediated signaling (24). In addition, an OTU (ovarian tumor domain) containing deubiquitinating enzyme, CYLD, dissociates Lys 63 -linked ubiquitin moieties from RIG-I, and therefore negatively regulates RIG-Imediated signaling (25,26). The ubiquitination/deubiquitination systems also target other components in the virus-triggered pathways.…”
mentioning
confidence: 99%